2023
DOI: 10.1515/jmbm-2022-0276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the tensile and bending strengths of the joints of “Gigantochloa apus” bamboo composite laminated boards with epoxy resin matrix

Abstract: The need for wood in the ship building industry continues to grow every year. An alternative raw material is needed to replace wood at a more affordable price, namely, bamboo laminated boards. However, bamboo has a weak connection between its segments, with a maximum length between components of less than 40 cm. To reduce these weaknesses, the connection between bamboo segments with laminated boards is carried out as follows: scarf joint, butt joint, finger joint, desk joint, and tongue and groove joint. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The Tsai-Hill criterion indicates that as the fiber orientation angle increases from 0°, the composite's tensile and compressive properties will continue to decline [37]. Sımılar result can be found in the previous study that laminated bamboo materials achieve the highest tensile strength with the laminates' direction 0° (on-axis laminates) compared to 45°/−45° and 0°/90° layer orientations [12,19]. The flexural strength in the present study is lower than in previous studies due to the use of thicker bamboo.…”
Section: Results Of Mechanical Testsmentioning
confidence: 90%
See 2 more Smart Citations
“…The Tsai-Hill criterion indicates that as the fiber orientation angle increases from 0°, the composite's tensile and compressive properties will continue to decline [37]. Sımılar result can be found in the previous study that laminated bamboo materials achieve the highest tensile strength with the laminates' direction 0° (on-axis laminates) compared to 45°/−45° and 0°/90° layer orientations [12,19]. The flexural strength in the present study is lower than in previous studies due to the use of thicker bamboo.…”
Section: Results Of Mechanical Testsmentioning
confidence: 90%
“…To enhance the strength properties of the material, it is recommended to use thinner bamboo that is laminated with a higher number of bamboo layers, as suggested by ref. [12]. Furthermore, the research found that laminated boards without joints and a fiber direction of 0° showed the highest strength, while those with a fiber direction of 45° or 90° experienced a decrease in tensile strength of 52% and 15.7%, respectively.…”
Section: Results Of Mechanical Testsmentioning
confidence: 93%
See 1 more Smart Citation